The Implications Of Mpb Structural Transformation On Tv Programming - Sabran, R (NATL Univ Malaysia, Fac Social Sciences & Humanities, 2024)
This paper focuses on the transformation of media organisations in Malaysia and the implications on media content through the debate of the political economy of media and globalisation of media content. The objectives of this study are to look at the aftermath of Media Prima Berhad's structural changes since the 1998 economic crisis and the transformations that occurred in the local broadcasting and content industries. Additionally, the identification of the implications of MPB transformation on its content, particularly the television programming of its four television stations will be discussed. Semi-structured interview and content analysis of TV programming approach were used to gather data. Two main findings were identified. MPB's corporate expansion had concentrated the local television market. The adoption of a cost-saving strategy and sharing of resources have been the keys to success. MPB is an integrated media organisation that has performed horizontal and vertical integration to strengthen its performance within the local broadcasting industry. Repositioning of 8TV and TV9 has transformed the stations' programming since conglomeration, whilst Chinese and religious programming emerged from the corporate expansion strategy.